Electronic Current Distribution Calculation for a Ni‐YSZ Solid Oxide Fuel Cell Anode. Issue 2 (1st February 2013) - Childs, N. B.; Law, C.; Smith, R.; Sofie, S.; Key, C.; Kopcyzk, M.; Lerch, M.
Abstract A simulation of a nickel‐yttrium stabilized zirconium oxide (Ni‐YSZ) solid oxide fuel cell cermet anode was used to determine the electronic current distribution within the percolating networks of nickel particles distributed in the electrode. The anode is simulated via a Monte–Carlo percolation model and current distribution is calculated via a relaxation algorithm. Nickel particle current densities are reported as a ratio to the total anode current density allowing results to be applied to any anode current density. Calculated current distributions were drastically affected by the volume percent of nickel as well as anode porosity. Experiments were performed to determine failure current densities of thin nickel wires to establish the relationship between critical current densities and surface area or volume of the wires. Both reducing and oxidizing environments were used for these measurements over a temperature range up to 800 °C.